Analytical and Clinical Evaluation of “AccuPower SARS-CoV-2 Multiplex RT-PCR kit (Bioneer, South Korea)” and “Allplex 2019-nCoV Assay (Seegene, South Korea)” for SARS-CoV-2 RT-PCR Diagnosis: Korean CDC EUA as a Quality Control Proxy for Developing Countries - Freire-Paspuel, Byron; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2021)
Background. Multiple RT-qPCR kits are available in the market for SARS-CoV-2 diagnosis, some of them with Emergency Use Authorization (EUA) by FDA or their country of origin agency, but a lot of them lack of proper clinical evaluation. Objective. We evaluated the clinical performance of two Korean SARS-CoV-2 RT-PCR kits available in South America, AccuPower SARS-CoV-2 Multiplex RT-PCR kit (Bioneer, South Korea) and Allplex 2019-nCoV Assay (Seegene, South Korea), for RT-qPCR SARS-CoV2 diagnosis using FDA EUA 2019-nCoV CDC kit (IDT, USA) as gold standard. Results. We found strong differences among both kits clinical performance and analytical sensitivity; while the Allplex 2019-nCoV Assay has sensitivity of 96.5% and an estimated a limit of detection of 4000 copies/mL, the AccuPower SARS-CoV-2 Multiplex RT-PCR kit has a poor sensitivity of 73.5% and limit of detection estimated to be over 20.000 copies/mL. Conclusions. AccuPower SARS-CoV-2 Multiplex RT-PCR kit and Allplex 2019-nCoV Assay are both made in South Korea but EUA by Korean CDC was only granted to the later. Our results support that Korean CDC EUA should be considered as a quality control proxy for Korean SARS-CoV-2 RT-PCR kits prior to importation by developing countries to avoid unreliable diagnosis.